New route for synthesis of 3- and 5-caffeoylquinic acids via protected quinic acids - Kadidae, La Ode; Usami, Akira; Koyama, Tomoya; Honda, Mitsunori; Kunimoto, Ko-Ki (European Journal of Chemistry, 2015)
Caffeoylquinic acids (CQAs) are a group of the phenylpropanoids produced by certain plant species, which have various biological activities including antioxidant, antibacterial, anticancer, and others. Several synthetic routes have been developed using quinic acids (QAs) and caffeic acid derivatives as starting materials. In this study, alternative pathways of 3- and 5-CQAs preparation using protected quinic acids are described. Both CQAs were achieved by removal of the protecting groups of compound 9 and 18 with acid hydrolysis using dilute HCl solution. These compounds (9 and 18) are novel, resulted from esterification reaction of diacetyl caffeoyl chloride and protected quinic acids. The hydroxyl groups of quinic acid in this case were protected with 2,2-dimethoxy propane or tert-butyldimethylsilyl (TBS) chloride.